Pharmacotherapy of Patients with Mild Persistent Asthma: Strategies and Unresolved Issues - Montuschi, Paolo (Frontiers in Pharmacology, 2011)
In studies comparing regular versus on demand treatment for patients with mild persistent asthma, on-demand treatment seems to have a similar efficacy on clinical and functional outcomes, but it does not suppress chronic airway inflammation or airway hyper-responsiveness (AHR) associated with asthma. Data on the efficacy of a continuous treatment with inhaled corticosteroids (ICS) in preventing the progression of asthma are conflicting. There is the possibility that patients without a regular treatment with ICS may develop a more severe asthma associated with airway structural changes (remodelling) and a progressive loss of lung function. However, the possible clinical and functional consequences of persistent, not controlled, airway inflammation in patients with asthma have to be established. Assessment of asthma control should include inflammatory outcomes, such as fraction of exhaled nitric oxide and sputum eosinophil counts. Until the relationships between symptoms, lung function tests, AHR, airway inflammation, exacerbations and airway remodelling are clarified, regular treatment seems to be generally more appropriate than on-demand treatment to warrant a greater control of asthma. Select subgroups of patients with mild asthma who are well controlled by regular treatment might adopt the on demand treatment plan as an intermediate step towards the suspension of controller medication. The increasing evidence for heterogeneity of asthma, the growing emphasis on asthma subphenotypes, including molecular phenotypes identified by omics technologies, and their possible implications for different asthma severity and progression and therapeutic response, are changing the paradigm of treating patients with asthma only based on classification of their disease severity to a pharmacological strategy more focused on the individual asthmatic patient. Pharmacological treatment of asthma is going towards a personalized approach.